PENGEMBANGAN KOSA-KATA BAHASA ANAK USIA DINI MELALUI FILM ANIMASI - Masbur Masbur (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2024)
Language education is essential because it significantly influences a child's vocabulary development. Teachers are required to be creative in finding types of media to enhance the teaching and learning process. The use of animated films as a medium proves beneficial in fostering imagination, encouraging fantasy, and introducing new knowledge. Vocabulary helps children build a simple repertoire of words and retell stories they hear. One institution that develops language vocabulary through animated films is Kindergarten, which uses this medium to stimulate children's language vocabulary development. Based on this issue, this study focuses on understanding how animated films influence vocabulary development in children's language skills in Kindergarten. The purpose of this study is to analyze the impact of animated films on the vocabulary development of children's language skills. This research employs a qualitative field research method with a descriptive approach. The findings reveal that animated films have a significant impact on Kindergarten children's behavior, particularly in their ability to use words appropriately.